Proceedings of the First International Conference on Materials Engineering and Management - Management Section (ICMEMm 2018) 2019
DOI: 10.2991/icmemm-18.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Knowledge Sharing Among Academics in Tertiary Institutions

Abstract: There has been a rising concern with regard to an inadequate level of knowledge sharing among the academicians in tertiary institutions across the globe. Scholars argue that improving academic research and quality of education at these institutions greatly depends on the level of knowledge sharing practices among them. Thus, it is important to explore the potential barriers to such knowledge sharing. Accordingly, this paper reviews pertinent literatures on barriers to knowledge sharing and knowledge witholding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The results also successfully justified the gap in the previous study (Bolander et al, 2017;Erasmus et al, 2017;Farooq et al, 2017;Maghdomi and Keikha, 2017;Miiro and Otham, 2018;Mohammed, 2018;Mohammed et al, 2020) by showing the significant relationship between talent management, knowledge management, university transformation, academic climate, and higher performance in education. Hazelkorn (2017), Masa'deh et al (2017, Rambe and Mbeo (2017), Paisey and Paisey (2018), and Karim and Majid (2019) observed the importance of managing talent and knowledge in enhancing higher education performance in the modern globalization era. The study indicated that skills and knowledge management are significant factors in achieving higher education performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results also successfully justified the gap in the previous study (Bolander et al, 2017;Erasmus et al, 2017;Farooq et al, 2017;Maghdomi and Keikha, 2017;Miiro and Otham, 2018;Mohammed, 2018;Mohammed et al, 2020) by showing the significant relationship between talent management, knowledge management, university transformation, academic climate, and higher performance in education. Hazelkorn (2017), Masa'deh et al (2017, Rambe and Mbeo (2017), Paisey and Paisey (2018), and Karim and Majid (2019) observed the importance of managing talent and knowledge in enhancing higher education performance in the modern globalization era. The study indicated that skills and knowledge management are significant factors in achieving higher education performance.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge management involves represented capabilities, know-how, and organizational information, creating, and transferring expertise that results in competitive advantage (Hassan and Raziq, 2019). Organizational knowledge creates a competitive transformation (Karim and Majid, 2019). As a result, we come up with the following hypothesis: Hypothesis 3: Knowledge management is positively related to university transformation.…”
Section: Knowledge Managementmentioning
confidence: 95%
See 2 more Smart Citations
“…Knowledge sharing among the academics is crucial for promoting strategic plans, curriculums, collaborative research, administrative services, and academic excellence in HEIs ( Howell and Annansingh, 2013 ). However, knowledge hiding and hoarding are much common among the academics of these institutions ( Bari et al., 2019 ; Chalak et al., 2014 ; Goh and Sandhu, 2013 ; Hernaus et al., 2015 , 2019 ; Karim, 2019 , Karim, 2020 ; Karim and Majid, 2019 ; Muqadas et al., 2017 ; Ramjeawon and Rowley, 2017 ; Samdani et al., 2019 ; Yang and Ribiere, 2020 ). Apart from knowledge hoarding (i.e., unintentional knowledge withholding), academics intentionally hide knowledge from each other ( Karim, 2020 ).…”
Section: Introductionmentioning
confidence: 99%